2019
DOI: 10.1161/circulationaha.118.036606
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Clinical and Echocardiographic Outcomes From the NOTION Randomized Clinical Trial in Patients at Lower Surgical Risk

Abstract: Background: The NOTION trial (Nordic Aortic Valve Intervention) was designed to compare transcatheter aortic valve replacement (TAVR) with surgical aortic valve replacement (SAVR) in patients ≥70 years old with isolated severe aortic valve stenosis. Clinical and echocardiographic outcomes are presented after 5 years. Methods: Patients were enrolled at 3 Nordic centers and randomized 1:1 to TAVR using the self-expanding CoreValve prosthesis (n=145) or SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
180
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(200 citation statements)
references
References 31 publications
7
180
1
12
Order By: Relevance
“…In the most recently published clinical and echocardiographic results, the trial concluded after 5 years that no significant differences were observed between the two patient groups in terms of the composite rate of all‐cause death, stroke, or MI . Also after 5 years of follow up the surgical group were found to have experienced more new‐onset or worsening atrial fibrillation, however the TAVI treated patients were found to require more pacemaker implantations on average as well as higher rates of paravalvular leakage (PVL) . NOTION as a trial can be considered to have some limitations however due to its small population size and the fact that this population may not be fully reflective of low‐risk patients with aortic stenosis.…”
Section: Tavi In Low‐risk Patientsmentioning
confidence: 99%
“…In the most recently published clinical and echocardiographic results, the trial concluded after 5 years that no significant differences were observed between the two patient groups in terms of the composite rate of all‐cause death, stroke, or MI . Also after 5 years of follow up the surgical group were found to have experienced more new‐onset or worsening atrial fibrillation, however the TAVI treated patients were found to require more pacemaker implantations on average as well as higher rates of paravalvular leakage (PVL) . NOTION as a trial can be considered to have some limitations however due to its small population size and the fact that this population may not be fully reflective of low‐risk patients with aortic stenosis.…”
Section: Tavi In Low‐risk Patientsmentioning
confidence: 99%
“…TAVR using the Edwards Sapien XT prosthesis was found to be non-inferior to conventional surgery for the primary endpoint death and disabling stroke in intermediate risk patients; however, trialists found a higher rate of significant (≥moderate) paravalvular leakage with TAVR vs. SAVR. NOTION (Nordic Aortic Valve Intervention) was an all-comers trial investigating TAVR vs. SAVR and found lower rates of kidney injury, bleeding, and new-onset atrial fibrillation among patients undergoing TAVR (14). Similarly, also the SURTAVI (Surgical Replacement and Transcatheter Aortic Valve Implantation) trial using the self-expanding CoreValve or Evolut R prosthesis proved safety and efficacy of TAVR in intermediate surgical risk patients (15).…”
Section: The Evolution Of Tavr-evidence According To Surgical Riskmentioning
confidence: 99%
“…De estos, 82% presentaba riesgo quirúrgico bajo (evaluado mediante un score predictor de mortalidad de la Sociedad de Cirujanos Torácicos [STS-PROM] menor a 4%). En el seguimiento a cinco años no hubo diferencias significativas en el objetivo final primario de muerte por cualquier causa, accidente cerebrovascular (ACV) e infarto (39,2% para TAVI vs 35,8% para cirugía, p=0,78) (6) .…”
Section: Transcatheter Aortic-valve Replacement With a Balloon-expandunclassified